SMART CITIES AND HEALTH INFORMATICS: TRANSFORMING URBAN HEALTHCARE SYSTEMS - Milić, Marko Kimi; Sinanović, Šćepan; Ratković, Milena; Eminović, Mithat (Medical Gazzette, 2026)
The integration of health informatics into smart cities offers a transformative approach to addressing the challenges of urban healthcare systems. This study evaluates the potential of health informatics in enhancing healthcare delivery, optimizing public health, and addressing inefficiencies in urban settings while identifying barriers to its implementation.The Introduction highlights the development of smart cities and positions health informatics as a critical tool for managing urban healthcare demands, including aging populations and chronic disease prevalence.The Theoretical Framework and Literature Review explores technologies such as IoT, Big Data, and AI, alongside case studies from Singapore and Barcelona that demonstrate improved healthcare outcomes.The Methodology employs a mixed-methods approach, including a systematic literature review and case study analysis in cities such as Amsterdam and Tokyo.The Results show a 40% reduction in emergency response times and a 25% decrease in chronic disease hospitalizations, while challenges such as data privacy, high costs, and interoperability persist.The Discussion emphasizes the importance of robust privacy frameworks, public-private partnerships, and inclusive strategies for improving digital literacy.The study concludes with the transformative potential of health informatics to build resilient and efficient urban healthcare systems, with recommendations for future research.
Keywords: Smart cities, health informatics, IoT, urban healthcare, public health.